The aetiology of pain in chronic midportion Achilles tendinopathy - Mkumbuzi, Nonhlanhla Sharon (Department of Human Biology, 2022)
Background Achilles tendinopathy (AT) is a common injury in athletes and sedentary individuals, which presents as pain and loss of function in the lower limb. Tendon pathology can exist without pain, but the hallmark of the condition is pain, which is classically of insidious onset, related to loading activity and often resistant to treatment. While the biology of pain in general is well described, the mechanisms of pain in AT are not fully understood. Most commonly, the nociceptive driver associated with AT is thought to be a result of the structural changes that occur in the tendon or the inflammatory cascades that occur in the pathological tendon and/or reflective of altered central pain mechanisms. Evidence from other chronic pain conditions also shows that genetic variation explains, at least in part, some of the heterogeneity observed in chronic pain conditions. The presentation of chronic Achilles tendon pain is variable and therefore it is reasonable to propose that this variability may be influenced by a genetic component. The absence of a definitive cause or mechanism of pain in AT is reflected in the plethora of treatment strategies available to manage it, most of which are not universally effective. In order to improve the management of pain in chronic AT, it is imperative that its mechanisms be better understood. Aims of the thesis The aims of this thesis were therefore to characterise Achilles tendon pain using other pain questionnaires, to investigate the relationship between structural changes and central pain mechanisms with self-reported tendon pain. Additionally, the thesis sought to evaluate the relationship between selected gene variants and pain in a cohort of recreational athletes with chronic Achilles tendinopathy using a candidate gene approach. Candidate genes: COMT rs4818 (C/G), COMT rs4633 (C/T), TAC1rs2072100 (C/T), TACR1 rs3771829 (C/G) and SCN9A rs6746030 (G/A) were selected based on the biological function of their encoded proteins within the pain pathways. The objectives of the specific chapters which addressed these aims were: • Describe Achilles tendon pain using multidimensional pain scales; the short forms of the McGill pain questionnaire (sf-MPQ) and Brief Pain Inventory (sf-BPI), as well as the Victorian Institute of Sports Assessment – Achilles questionnaire (VISA-A) (Chapter 2). • Evaluate the relationship between self- reported tendon pain, the grey scale ultrasound and colour Doppler characteristics in chronic AT (Chapter 3). • Evaluate the relationship between conditioned pain modulation and chronic AT (Chapter 4). • Explore and evaluate if variants in genes [COMT rs4818 (C/G), COMT rs4633 (C/T), TAC1 rs2072100 (C/T), TACR1 rs3771829 (C/G) and SCN9A rs6746030 (G/A)] involved in the pain pathways are associated with either self-reported tendon pain and/or conditioned pain modulation (Chapter 5). Methods Two hundred and eighty-two (282) recreational athletes with at least one year's experience in their main sport were recruited for the studies in this thesis but fifty-two (52) were excluded for not meeting the inclusion criteria of the studies. Hence, 103 recreational athletes without a history of chronic AT (CON) and 127 participants clinically diagnosed with chronic AT (TEN) were included in the study. All participants completed demographic questionnaires on their medical, sporting, training, and injury history. Participants with AT (TEN) also completed the self-administered eight question VISA-A questionnaire, the sf-MPQ and the sf-BPI. Additionally, all participants had grey scale ultrasound (US) and colour Doppler (CD) assessments of both their tendons performed and had conditioned pain modulation (CPM) assessed using pressure and cold pain. Lastly, participants were genotyped for variants in COMT rs4818 (C/G), COMT rs4633 (C/T), TAC1 rs2072100 (C/T), TACR1 rs3771829 (C/G) and SCN9A rs6746030 (G/A) using standard PCR methods. Data were analysed using Statistica Version 13.2.50. Normality of data was assessed using the Shapiro-Wilks test. Evaluations of differences between normally distributed quantitative data were conducted with the independent students t-test or one-way ANOVA, while Mann-Whitney-U and Kruskall-Wallis tests were used for non-normally distributed data. The Fisher's exact and χ2 tests were used for categorical data. For post-hoc analyses, the Kruskal-Wallis associated multiple comparisons test with Bonferroni adjustment was used for quantitative data. For the genotyping data, Hardy– Weinberg equilibrium (HWE) was calculated using ‘HardyWeinberg' version 1.6.3. package. The overall level of significance was set at p<0.05. Results From the sf-MPQ, the most frequent descriptors in the sensory index were ‘aching' (n=73, 60.3%), ‘tender' (n=64, 52.9%) and ‘throbbing' (n=41, 33.9%). Words from the affective index of the sf-MPQ were seldom used to describe tendon pain. From the sf BPI, in addition to interfering with walking ability, AT pain also interfered with mood (n=61, 50.8%), sleep (n=40, 34.8%) and relationships with others (n=30, 25.0%). Additionally, there were weak to moderate correlations between corresponding indices on the sf-MPQ, VISA-A and sf-BPI (r2>0.3; p<0.05) and the VISA-A scores were lower when participants reported severe tenderness (p=0.005), sharp (p=0.030) and/or stabbing pain (p=0.048) on the sf-MPQ. On US and CD, the TEN participants had thicker tendons [median (IQR)] [TEN 6.3mm (5.4 - 7.9) vs CON 5.5mm (4.8 - 6.0), p<0,001]; relative abnormal ultrasound appearances (TEN 48.7%, n=38 vs CON 22.4%, n=19, p=0.001) and had more neovessels (TEN 20.5%, n=16 vs CON 1.0%, n=1, p=0.001) (p<0.001) than the CON participants. In the TEN group, no significant differences were noted between the self reported total pain scores of the sf-MPQ, sf-BPI and VISA-A scales or their separate indices and tendon diameter, US abnormalities or presence of neovessels (p>0.05). However, the median interference index scores of the VISA-A questionnaire of participants with US abnormalities [median (IQR)] [35.5 (30.0 - 41.0), n=36] was significantly higher than those without US abnormalities [32.5 (26.0 - 37.0), n=39, p=0.046]. Additionally, participants from the TEN group who reported no stabbing pain, those who reported mild, moderate or severe stabbing pain on the sf-MPQ had significantly thicker tendons [median (IQR)] [6.0mm (5.2 - 7.6) vs 7.0mm (5.9 - 8.9), 7.7mm (6.2 - 9.1) and 6.3mm (4.9 - 7.4), p=0.037]. From the CPM analysis, participants with tendinopathy had a lower pressure pain threshold (PPT) before [median (IQR)] [TEN: 417kPa (364 - 516) vs CON 601kPa (459 - 724), p<0.001] and during [TEN: 458kPa (358 - 550) vs CON 633kPa (506 - 753), p<0.001] the cold pressor test. However, there was no difference in the CPM effect between the two groups [median (IQR)] [TEN: 34kPa (-2 - 79) vs CON: 45kPa (4 - 94), p=0.490]. From the sf-BPI, PPT before the cold pressor test were significantly lower in individuals who reported mild to severe interferences in mood (p=0.023), general activity (p=0.038) and walking ability (p=0.004) when compared to those who reported no interferences. Pressure pain thresholds before the cold pressor test were also significantly lower in those participants who reported mild to severe pain at the time of testing (p=0.024) or reported moderate to severe pain on average (p=0.014) on the sf- BPI. Additionally, from the sf-BPI, a low CPM effect was significantly associated with mild to severe interference with sleep (p=0.043). The genotype analysis showed that the median total scores of self-reported tendon pain from the sf-MPQ were significantly different (p=0.019) among the three COMT rs4818 (G/C) genotype groups [median (IQR)] [CC: 9.1 (4.0 - 13.0) n=61; CG: 7.3 (4.0 - 0.0) n=50; GG: 4.0 (1.0 - 5.0) n=7], with the CC genotype having a significantly higher pain score (p=0.018) than the GG genotype. No other associations were observed between genotype distributions of COMT rs4633, TAC1 rs2072100, TACR1 rs3771829, SCN9A rs746030 and the median self-reported total tendon pain scores for the sf-MPQ, sf-BPI, VISA-A, or their subscales. Conclusion The novel findings of this thesis suggest that the language of chronic AT pain ought to be further investigated as it may help extend our knowledge of the underlying mechanisms in chronic AT pain. In addition, that AT pain interferes with more than physical and sporting ability should be considered in the overall management of this condition in athletes. While no associations were observed between imaging findings and tendon pain, the relationship between imaging findings and physical limitations suggests that using pain as a primary outcome measure in rehabilitation may be insufficient and highlights the need to further study the relationship between tendon structure, imaging and pain. Furthermore, impaired CPM was associated with interferences with sleep which suggests that, though not quite clear, some central mechanisms are at play in chronic AT pain. This finding also reaffirms the need to consider factors other than physical function in AT management. Another novel finding of this thesis was the association between COMT rs4818 (C/G) and chronic tendon pain. This finding suggests that the catecholaminergic pathway is involved in the chronic AT pain pathway. COMT variants are associated with maladaptive coping mechanisms which may be important to consider in managing chronic pain conditions such as AT. In future, larger studies are required in order to replicate these findings and large, prospective cohort studies are required to confirm the role of genetic variation in chronic AT pain. Overall, the mechanisms of pain in tendinopathy are complex and not yet well described, emphasising the further need for multi-sectorial research.